Fermentasi etanol menggunakan bakteri Zymonas mobilis dari glukosa hasil hidrolisa enzimatik bagas - S Saraswati (Jurnal Teknik Kimia Indonesia, 2007)
The resources and reserves of oil which is a non renewable energy are very limited, while the oil consumption is increasing continuously. It is necessary to look for alternative energy. Etanol, a liquid energy, is a renewable alternative energy. Glucose can be used as raw material for etanol production. Glucose can be obtained by enzymatic hydrolysis of bagasse which is a solid waste of sugar canefactory. The objective of this research was to get the optimum condition of etanol production using bagasse as raw material. The experimental research consisted of 2 steps. First step : enzymatic hydrolysis of bagasse with chemical pretreatment process, and the second step was fermentation process using Zymomonas mobilis bacteria. Variables of thefirst step were the NaOH concentration (5%, 7% and 9%) as a pretreatment agent, and cellulase enzyme used (30, 40 and 50 cellulase enzyme  units/gram bagasse). For the second step, the variables were glucose concentration (I2.5%, 15%, 20%, 22.5%, and 25%) and the fermentation time (20, 24, 28, 32, 36, 40 and 48 hours). The experiment showed that the best result of the enzymatic hydrolysis could be obtained by NaOH 7% as chemical pretreatment agent and using 50 units of cellulase enzyme/gram bagasse. The cellulose conversion of bagasse was 87% within 42 hours period time. The highest etanol concentration of the fermentation process was 9.238% (weight %) and the yield was 0.4912 grams etanol/gram glucose. It was reached by using 22.5% glucose during 48 hours fermentation  time.Keywords: etanol; fermentation; Zymomonas mobilis; glucose; hydrolysis; cellulase enzyme; pretreatment;bagasse AbstrakCadangan minyak bumi yang merupakan non renewable energy (energi tak terbarukan) sangat terbatas, sedang konsumsinya terus meningkat.  Untuk itu perlu  dicari energi alternatif. Etanol merupakan salah satu energi cair alternatif yang terbarukan (renewable). Bahan baku etanol antara lain adalah glukosa. Glukosa dapat diperoleh dari hidrolisa enzimatik bagas yang merupakan limbah pabrik gula. Penelitian ini bertujuan  untuk  mendapatkan  kondisi yang  optimum  dari pembuatan  etanol  dengan  bahan baku bagas. Penelitian  experimental  meliputi  dua tahap.  Tahap I  : proses  hidrolisa  enzimatik  dari bagas dengan perlakuan pendahuluan  (pretreatment), dan tahap II adalah proses fermentasi  dengan bakteri Zymomonas  mobilis.  Variabel pada  tahap I  adalah  konsentrasi  NaOH  sebagai  pretreatment   agent sebesar 5%, 7% dan 9% serta pemakaian enzim selulase : 30, 40 dan 50 unit enzim selulase/gram bagas. Variabel untuk tahap II  adalah konsentrasi glukosa:  12.5%,  15%, 20%, 22.5%  dan 25% dan waktu fermentasi  20, 24, 28, 32, 36, 40  dan 48 jam.  Hasil penelitian  menunjukkan  bahwa  untuk  hidrolisa enzimatik hasil yang terbaik diperoleh dengan NaOH 7% dan 50 unit enzim selulase/gram bagas dengan konversi selulosa 87% dan waktu 42 jam. Untuk fermentasi kadar etanol tertinggi diperoleh pada konsentrasi glukosa 22.5% yaitu sebesar 9.238%, waktu 48 jam dan yield 0.4912 gram etanollgram glukosa.Kata Kunci: etanol; fennentasi; Zymomonas mobilis; glukosa; hidrolisa ; enzim selulase; pretreatment; bagas.